Proteinase Activity during Tracheary Element Differentiation in Zinnia Mesophyll Cultures. - Beers, E. P. (1997)
The zinnia (Zinnia elegans) mesophyll cell culture tracheary element (TE) system was used to study proteinases active during developmentally programmed cell death. Substrate-impregnated gels and single-cell assays revealed high levels of proteinase activity in differentiating TEs compared with undifferentiated cultured cells and expanding leaves. Three proteinases (145, 28, and 24 kD) were exclusive to differentiating TEs. A fourth proteinase (59 kD), although detected in extracts from all tissues examined, was most active in differentiating TEs. The 28- and 24-kD proteinases were inhibited by thiol proteinase inhibitors, leupeptin, and N-[N-(L-3-trans-carboxirane-2-carbonyl)-L-leucyl]-agmatine (E-64). The 145- and 59-kD proteinases were inhibited by the serine proteinase inhibitor phenylmethylsulfonyl fluoride (PMSF). Extracts from the TE cultures contained sodium dodecyl sulfate-stimulated proteolytic activity not detected in control cultures. Sodium dodecyl sulfate-stimulated proteolysis was inhibited by leupeptin or E-64, but not by PMSF. Other tissues, sucrose-starved cells and cotyledons, that contain high levels of proteolytic activity did not contain TE-specific proteinases, but did contain higher levels of E-64-sensitive activities migrating as 36- to 31-kD enzymes and as a PMSF-sensitive 66-kD proteinase.